KAJIAN KUAT TEKAN BETON FC’30 DAUR ULANG DENGAN MENGGUNAKAN AGREGAT EX MSE WALL (CORNESTONE) - Winata, Wiyeo; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
In this research method used is the experimental method, namely, the method used to find the effect of certain treatments on others under controlled conditions and for testing using destructive methods, namely by destroying the test object being studied. In this research, the test object variables used 27 compressive strength test specimens, cylindrical test specimens with a diameter of 15 cm x 30 cm high. This research used FC'30 concrete quality, to analyze the comparative compressive strength between normal FC'30 concrete and FC concrete. '30 uses recycled cornestone as an additive to the concrete mixture, the compressive strength test on this test object is carried out when the test object specimen is 7 days old, 14 days old and up to 28 days old. Compressive strength is the ability of concrete to accept compressive force per unit area. From the results of the compressive strength test, a graph of the relationship between the additions was created. Cornestone aggregate on compressive strength and analyze the comparison of compressive strength between normal FC'30 concrete, recycled and cornestone.Keywords : Study of Recycled Fc'30 Concrete Compressive Strength Using Ex MSE WALL (Cornestose) Aggregate.